2004
DOI: 10.1111/j.1574-6968.2004.tb09620.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of drug resistance in intestinal lactobacilli of dairy and human origin in Turkey

Abstract: The prevalence of different resistance genes was investigated in lactobacilli of human and dairy origin by PCR. The presence of erm, van, tet, and cat-TC genes were determined in 16 raw milk, 15 cream, 10 yogurt, 50 hand-made cheese, and 20 industrially produced white-cheese samples of dairy origin and 16 mouth, 32 fecal, and 36 vaginal samples from different subjects of human origin. Lactobacilli of dairy and human origin were found to carry only erm(B) and tet(M) genes. The majority of the isolates, Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 37 publications
5
26
1
Order By: Relevance
“…Differential susceptibility to vancomycin may be helpful in speciation of lactobacilli. The finding that all the strains tested in the present study were resistant to this antibiotic is in accordance with the results of Hamilton-Miller and Shah [20] and with previous studies, which have shown that the vancomycin resistance in lactobacilli is intrinsic and chromosomally encoded [11].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Differential susceptibility to vancomycin may be helpful in speciation of lactobacilli. The finding that all the strains tested in the present study were resistant to this antibiotic is in accordance with the results of Hamilton-Miller and Shah [20] and with previous studies, which have shown that the vancomycin resistance in lactobacilli is intrinsic and chromosomally encoded [11].…”
Section: Discussionsupporting
confidence: 82%
“…Finally, Çataloluk and Gogebakan [11] pointed out that the presence of the resistance genes in the majority of the lactobacilli of intestinal origin suggests that transfer of such genes from an unknown origin during the passage from the intestinal tract is more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However contradictory to this, resistance to tetracycline is reported as the most frequent among lactobacilli [11,12]. Earlier reports by a number of authors [8,[13][14][15] ranking the resistance genes, tet(M) for tetracycline resistance as most common in LAB also supports the prevalence of tetracycline resistance in LAB. However in the present study all the isolates were found to be sensitive to this particular antibiotic.…”
Section: Issn: 2474-4530mentioning
confidence: 85%
“…There is an observation that tet(M) gene is the most frequently found tetracyline resistance determinant in LAB [71]. The widespread distribution of tet(M) among members of L. plantarum, L. curvatus, L. casei, L. acidophilus, L. gasseri and L. crispatus was reported by several authors [46,71,72]. Ammor et al [73] confi rmed coexistence of two tetracycline resistance genes tet(M) and tet(K) in a foodborne strain of Lactobacillus sakei.…”
Section: Discussionmentioning
confidence: 96%